2022-RA-128-ESGO Ultrasound assessment of pathological lymph nodes in gynecologic cancers. (20th October 2022) - Elagwany, Ahmed
Abstract : Introduction/Background: Lymph nodes can be affected in gynecologic cancers and they are uplifting the stage of cancer. They are a poor prognostic factor for cancers. They usually need radiotherpay if they are affected by metastasis. Usually they are detected by CT scan and MRI during assessing any pelvic malignancy. Ultrasound can be used for detecting suspicious nodes. We are aiming here to spot the light over this and showing a pictorial essay for nodes detected on ultrasound Methodology: Nodes are pathological on stage 3 cancer vulva (of inguinal ones and stage 4 if pelvic ones), stage 3 endometrial cancer (in pelvic ones and stage 4 if inguinal ones or scalene ones), Stage 3 cancer cervix (if pelvic and stage 4 if paraaortic ones), Stage 3 cancer ovary for pelvic and paraaortic ones. The approach for visualizing lymph nodes starts at the inguinal canal and proceeds towards the diaphragm. A transvaginal examination visualize lymph nodes related to external iliac vessels and the obturator fossa. Results: Pathological nodes involved by metastasis has a peripheral or mixed perfusion as an early sign. The shape of an infiltrated lymph node is round, with loss of the hilum sign and inhomogeneous and hypoechogenic. Necrosis, calcification or lymph-node deposits produce a heterogeneous pattern. Later, there is extracapsular growth and irregular margin. Lymph nodes can have a large size more than 2 cm but it is not correlated to malignancy. Nodes are assed based in shape, echogenicity, regularity, homogencity and vascularity. Usually if 2 abnormal signs are seen on ultrasound, this indicates a pathological node apart from size. Conclusion: Ultrasound can be used in assessing lymph nodes.